2020
DOI: 10.18332/tid/123429
|View full text |Cite
|
Sign up to set email alerts
|

Smoking history and its relationship with comorbidities in patients with obstructive sleep apnea

Abstract: INTRODUCTION Current knowledge on the correlation between smoking and comorbidities associated with obstructive sleep apnea (OSA) is limited. This study evaluated the smoking history of OSA patients and analyzed the association between smoking and OSA comorbidities. METHODS Retrospective analysis was performed in newly diagnosed OSA patients in our hospital, a tertiary medical center, from January 2016 to December 2019. In all, 1021 patients were enrolled and divided into two groups, nonsmokers (n=796) and cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
3
13
2
Order By: Relevance
“…Our results are in line with the observations of Bielicki et al [6] that also showed that the proportion of non-smokers with OSA with HTN was higher than that of ever-smokers. Contrary to our findings, Shao et al found a significant increase of HTN risk in current/former smoking patients with OSA [45]. This variation could be related to the differences of the populations studied.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are in line with the observations of Bielicki et al [6] that also showed that the proportion of non-smokers with OSA with HTN was higher than that of ever-smokers. Contrary to our findings, Shao et al found a significant increase of HTN risk in current/former smoking patients with OSA [45]. This variation could be related to the differences of the populations studied.…”
Section: Discussioncontrasting
confidence: 99%
“…In a like matter, in another retrospective analysis, no significant differences in the AHI were found when comparing current/former smokers with non-smokers. However, current/former smokers presented lower nocturnal mean oxygen saturation [45]. Opposite to our findings, these three latter studies [6,44,45] reported higher daytime sleepiness (ESS) in smokers that was attributed to the combined effects of nicotine on sleep architecture, on the upper airway and possibly to nocturnal hypoxia.…”
Section: Discussioncontrasting
confidence: 77%
“…In terms of symptoms, the main difference was noticed in daytime sleepiness and the Epworth score. In agreement with previous research [29], the Epworth scores are directly related to the AHI.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that smoking was reported in 23.5% of our sample, but smoking was not associated with increased AHI severity category. Previous research has established that smoking can negatively affect certain physiological sleep parameters by increasing sleep latency and reducing nocturnal oxygen saturation [ 84 ]. This result was not consistent with findings of previous studies that smoking was related to OSA severity [ 85 , 86 ], but was in accordance with other negative findings [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%